Effect of avatrombopag in the management of severe and refractory chemotherapy-induced thrombocytopenia (CIT) in patients with solid tumors. (3rd October 2022) - Gao, Yanting; Liu, Qi; Shen, Yingying; Li, Yuzhu; Shao, Keding; Ye, Baodong; Shen, Yiping; Zhou, Yuhong; Wu, Dijiong
Abstract: Chemotherapy-induced thrombocytopenia (CIT) is a common complication in cancer patients, especially after multiple cycles of chemotherapy, which leads to the delayed treatment or reduced dosage. The treatment of CIT is limited for refractory and severe cases. Herein we reported a single-center study of avatrombopag, a type of thrombopoietin receptor agonist (TPO-RA), for the treatment of severe and refractory (S/R) CIT who failed from multi-line treatments. A total of 13 cancer patients with S/R CIT were enrolled at the First Affiliated Hospital of Zhejiang Chinese Medical University from September 2020 to February 2021. All the patients were administered oral avatrombopag at an initial dose of 60 mg/day, which could be decreased as needed, over a period of 8 weeks. Eight (8/13, 61.5%) patients responded to avatrombopag (with a platelet count ≥50 × 10 9 /L and transfusion independent), with a median response time of 27.5 (11–50) days, and the median cumulative day of platelet response was 79 (20–167). Ten of 13 patients (76.9%) no longer required platelet transfusion at the study endpoint. The predictor of response was the level of hemoglobin (HB) at study entry, patients with an HB over 90 g/L achieved a response rate of 88.9%. In addition, platelet count showed 87.5% sensitivity and 100% specificity to predict the treatment response at a cutoff value of 25.5× 10 9 /L at the end of the third week management. No drug-related side effects were noticed during administration. Our study showed that avatrombopag could be a novel and effective drug for the treatment of severe and refractory CIT, especially for those with hemoglobin above 90 g/L. This study was registered at chictr.org.cn as # ChiCTR2100050646.